ANTIBACTERIAL ACTIVITY OF SPONGE ASSOCIATED-BACTERIA ISOLATED FROM NORTH JAVA SEA - Ocky Karna Radjasa (JOURNAL OF COASTAL DEVELOPMENT, 2007)
A total of 90 bacterial isolates were obtained from association with sponges collected from Bandengan water, Jepara and Karimun island of Karimunjawa islands in the north java sea. Antibacterial screening by using a pathogenic Escherichia coli indicated that two isolates BSP.12 and MKSP.5 inhihited the growth of tested strain. Molecular identification based on 16S rDNA approach revealed that isolate BSP.12 was closely related to Vibrio harveyi with a homology of 100% and isolate MKSP.5 showed highest similarity to Brachybacterium rhamnosum (99%), respectively.A PCR-based approach by using specific primers targeting the occurrence of gene fragments necessary for the biosynthesis of major natural products, namely Non-ribosomal peptide synthetases (NRPS) and Polyketide synthases (PKS) was applied to estimate the genetic potential of these active strains. Both isolates were capable of amplifying the NRPS gene fragments but not the PKS gene fragments.